Intensitas Bermain Game Online jenis First-Person Shooter dan Agresivitas pada Siswa SMP - Hillary Bestari Setyawijaya; Agnes Indar Etikawati (Merpsy Journal, 2026)
This study examined the relationship between the intensity of playing First-Person Shooter (FPS) online games and aggressiveness among junior high school students. The study was conducted due to the increasing prevalence of aggressive behavior among adolescents and the growing popularity of FPS games that contain violent and competitive elements. It was hypothesized that there is a positive relationship between FPS online game playing intensity and aggressiveness. A quantitative correlational design was employed involving 191 junior high school students aged 11–16 years who actively played FPS online games. Data were collected using the FPS Online Game Playing Intensity Scale (12 items; α = .749), measuring frequency, duration, attention, and emotional involvement, and the Aggressiveness Scale (12 items; α = .704), assessing physical aggression, verbal aggression, anger, and hostility. Data were analyzed using Spearman’s rho correlation test due to non-normal data distribution. The results revealed a significant positive correlation between FPS online game playing intensity and aggressiveness (r = .669, p < .001). Additional analyses indicated that all dimensions of gaming intensity were significantly associated with aggressiveness. These findings suggest that higher FPS gaming intensity is related to higher aggressiveness among junior high school students, highlighting the importance of monitoring gaming behavior and promoting healthy gaming habits among adolescents